6‐Pyridinium benzo[a]phenazine‐5‐oxide derivatives as visible photosensitisers for polymerisation. (24th July 2014) - Podemska, Karolina; Podsiadły, Radosław; Orzeł, Agnieszka; Kowalska, Aleksandra; Maruszewska, Anna; Marcinek, Andrzej; Sokolowska, Jolanta
<x xml:space="preserve">Abstract</x> Several 6‐pyridinium benzo[a]phenazine‐5‐oxide derivatives have been synthesised and characterised by proton nuclear magnetic resonance spectroscopy and mass spectrometry. The spectroscopic and electrochemical properties of these dyes were examined. The dyes were used as reducible sensitisers for selected electron donors (phenylthioacetic acid, phenoxyacetic acid, N‐phenylglycine, and ethyl 4‐N, N‐dimethylaminobenzoate) and as oxidisable sensitisers for electron acceptors (onium and N‐alkoxypyridinium salts). These photoredox pairs were found to be effective visible‐wavelength photoinitiators for the free radical polymerisation of trimethylolpropane triacrylate under visible light. The cationic photopolymerisation of cyclohexene oxide by the studied dyes and the onium salt photoredox pairs was ineffective. The obtained results are discussed on the basis of both free energy change for electron transfer to or from the benzo[a]phenazine dyes and the photochemical properties of the dyes, particularly their photobleaching. The proposed mechanism of dye fading is supported by density functional theory calculations and spectroscopic characterisation of the radical cation of the dye.